2017
DOI: 10.1002/app.44712
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects on mechanical properties of microfibrillar composites with dual reinforcement: Explanation by FEA model of soft interface

Abstract: Nanofillers (NF) in microfibrillar composites support melt‐drawing and may lead to improved performance. However, antagonistic effects have also been found. The deterioration of mechanical properties by drawing in the presence of NF, as found by other authors in analogous undrawn systems, has not yet been explained. Experiments indicating the importance of NF migration between the HDPE matrix and the PA6 fibrils in the course of drawing have led to a tentative conclusion of changed crystallinity in the interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…While the addition of nanofiller decreases the J‐integral, the TIS is increased by the presence of nanofiller. At the same time, the fact that in these systems migration of GNP across the interface occurs (see 3.1) further confirms important effect of this phenomenon on MFC performance . The importance of the discussed differences in sample dimension/mold filling conditions is supported by the fact, that Charpy impact testing, done on the same samples as for J‐intergral, practically correspond to J‐integral, as shown in our previous works concerning MFC modified by nanoclay .…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…While the addition of nanofiller decreases the J‐integral, the TIS is increased by the presence of nanofiller. At the same time, the fact that in these systems migration of GNP across the interface occurs (see 3.1) further confirms important effect of this phenomenon on MFC performance . The importance of the discussed differences in sample dimension/mold filling conditions is supported by the fact, that Charpy impact testing, done on the same samples as for J‐intergral, practically correspond to J‐integral, as shown in our previous works concerning MFC modified by nanoclay .…”
Section: Resultssupporting
confidence: 73%
“…In all MFC with at least a part of GNP applied as the HDPE masterbatch and thus with some extent of GNP migration between the components, worse properties were found. This is ascribed to affecting of parameters of the interface by GNP localized in and/or migrating through this area, and by variation in the matrix crystallinity, as recently explained by the concept of reduced amount of spherulites near the fibre surface (soft interface) . Of importance is the fact that tensile impact strength is increased by fibrils formation but also by GNP; the contribution of GNP was also important in the undrawn system.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This could be caused by reduction of the matrix crystallinity in the vicinity of fibers. The second effect can lead to marked antagonistic effects on final mechanical behavior . We have recently showed that NF and their migration could also negatively affect the course of drawing and solidification and thus the matrix crystallinity near the interface .…”
Section: Introductionmentioning
confidence: 99%
“…The second effect can lead to marked antagonistic effects on final mechanical behavior . We have recently showed that NF and their migration could also negatively affect the course of drawing and solidification and thus the matrix crystallinity near the interface . Therefore, NF effects must be harmonized to achieve synergic instead of antagonistic effects on mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%